Assessing Asymptomatic, Presymptomatic, and Symptomatic Transmission Risk of Severe Acute Respiratory Syndrome Coronavirus 2. (27th March 2021) - Wu, Peng; Liu, Fengfeng; Chang, Zhaorui; Lin, Yun; Ren, Minrui; Zheng, Canjun; Li, Yu; Peng, Zhibin; Qin, Yin; Yu, Jianxing; Geng, Mengjie; Yang, Xiaokun; et al.
Abstract: Background: The relative contributions of asymptomatic, presymptomatic, and symptomatic transmission of severe acute respiratory syndrome coronavirus 2 have not been clearly measured, although control measures may differ in response to the risk of spread posed by different types of cases. Methods: We collected detailed information on transmission events and symptom status based on laboratory-confirmed patient data and contact tracing data from 4 provinces and 1 municipality in China. We estimated the variation in risk of transmission over time and the severity of secondary infections by symptomatic status of the infector. Results: There were 393 symptomatic index cases with 3136 close contacts and 185 asymptomatic index cases with 1078 close contacts included in the study. The secondary attack rates among close contacts of symptomatic and asymptomatic index cases were 4.1% (128 of 3136) and 1.1% (12 of 1078), respectively, corresponding to a higher transmission risk from symptomatic cases than from asymptomatic cases (odds ratio, 3.79; 95% confidence interval, 2.06–6.95). Approximately 25% (32 of 128) and 50% (6 of 12) of the infected close contacts were asymptomatic from symptomatic and asymptomatic index cases, respectively, while more than one third (38%) of the infections in the close contacts of symptomatic cases were attributable to exposure to the index cases before symptom onset. Conclusions: Asymptomatic and presymptomatic transmissions play an important role in spreading infection, although asymptomatic cases pose a lower risk of transmission than symptomatic cases. Early case detection and effective test-and-trace measures are important to reduce transmission. Abstract : Presymptomatic transmission of coronavirus disease 2019 (COVID-19) accounted for 38% of all infections that occurred from exposure to symptomatic cases. Asymptomatic severe acute respiratory syndrome coronavirus 2 infectors posed a lower risk to further transmission than symptomatic infectors.